Quercus suber cork extract displays a tensor and smoothing effect on human skin: an in vivo study. - Coquet, C; Bauza, E; Oberto, G; Berghi, A; Farnet, A M; Ferré, E; Peyronel, D; Dal Farra, C; Domloge, N (Drugs under experimental and clinical research, 2005)
Recently, it has become indispensable for anti-aging active ingredients to provide a visible and immediate smoothing antiwrinkle effect. In Quercus suber, suberin is the most important structural component of cork cell walls. Studies have shown that suberin is made up mostly of hydroxycarboxylic acids and that it is endowed with many special mechanical and chemical properties that evoke a possible smoothing effect on the surface of the skin. Therefore, we were interested in investigating the effect of this cork extract on the skin's surface in a double-blind clinical study. The study was conducted in 15 healthy volunteers, aged 22 to 52 years. The volunteers applied a gel formula with 3% of cork extract, or placebo gel, on each forearm. Skin surface roughness was evaluated visually by pictures and by silicone replicas 1 and 2 h after application, followed by statistical analysis using the matched-pairs McNemar statistical test. McNemar analysis of the pictures revealed that application of cork extract on the skin resulted in a highly significant reduction of roughness 1 h after application. This effect was observed in 73.3% of volunteers. Two hours after cork extract application, a highly significant improvement of skin roughness was found in 78.6% of volunteers. Moreover, silicone replica treatment confirmed significant improvement in average of roughness at 2 h. These results demonstrate that cork extract provides a remarkable and highly significant tensor and smoothing effect on the skin, which could be of great use in anti-aging skin care products.
Journal Article,Randomized Controlled Trial,
Keywords: 2; 3-friedelanol; 6-heptanediol; Quercus suber L.; suberin; Terpens

Annual dynamics of phosphatase activities in an evergreen oak litter: influence of biotic and abiotic factors - Criquet, S; Ferré, E; Farnet, A M; Le petit, J (Soil Biology and Biochemistry, 2004)
As part of a study of the processes involved in litter biodegradation, we considered the variations over 1 year of the phosphatase activities in sclerophyllous evergreen oak litter (Quercus ilex L.). Evergreen oak is representative of tree species in the forests of the French Mediterranean area. Acid (E.C. 3.1.3.2.) and alkaline (E.C. 3.1.3.1.) phosphatases, were measured over 13 months in the forest litter, along with several biotic and abiotic variables, potentially involved in the regulation of these enzymes. These comprised moisture, temperature, pH, water-extractable inorganic P (PI ), fungi, culturable heterotrophic bacteria and protein concentrations. Moisture considerably affected the production of proteins and acid phosphatases, probably formed by litter microorganisms. This result corroborated the study of Criquet et al. [Soil Biology and Biochemistry 34 (2002) 1111] which indicated that rainfall was the most important factor regulating the production and the activity of numerous enzymes in sclerophyllous forest litter. However, it appeared that moisture cannot alone predict all of the variations in phosphatase activities and the mineralisation rate of organic P (PO). Indeed, principal component analyses (PCA) and multiple regressions showed that temperature and bacterial communities were also implicated in phosphatase dynamics and PO mineralisation. Acid phosphatases were negatively correlated with the temperature, whilst alkaline phosphatases were positively correlated with this variable. The signiﬁcant correlation obtained between bacteria and PI concentrations, and the lack of correlation between bacteria and both acid and alkaline phosphomonoesterases, suggest that other important phosphatase types, such as phosphodiesterases, must be strongly implicated in PO mineralisation of the litter and in the regulation of P microbial metabolism.
Keywords: biodegradation; phosphatases; phosphate; phosphomonoesterases; phosphorus transformations; Quercus ilex

Purification of a new isoform of laccase from a Marasmius quercophilus strain isolated from a cork oak litter (Quercus suber L.) - Farnet, A M; Criquet, S; Pocachard, E; Gil, G; Ferré, E (MYCOLOGIA, 2002)
A new isoform of laccase from Marasmius quercophilus is described in this study. The strain of this white-rot fungus was isolated for the first time on a cork oak litter. This isoform exhibited certain common properties of laccases (a molecular weight of 65 Kda, an optimum pH of 6.2 with syringaldazine). But this laccase has also particularly novel features: the best activity measured was observed at high temperatures (80 C) and this isoform was not inhibited with EDTA. Furthermore, this induced laccase was able to transform most of the aromatic compounds tested without the addition of mediators to the reaction mixture, and the transformation of certain chlorophenols (2-chlorophenol and 2,4-dichlorophenol) by a laccase isoform from M. quercophilus is reported here for the first time. We also demonstrate the importance of 2,2'-azinobis(3-ethylbenzthiazoline-6-sulfonate) (ABTS) as a mediator since it allowed veratryl alcohol and p-hydroxybenzoic acid transformation. Moreover, new products of transformation were observed using the combination of ABTS with this isoform of laccase.
Keywords: aromatic compounds; mediator; polyphenoloxidase; white-rot fungus